Representasi Makna Kematian pada Individu dalam Perspektif Keislaman - Brian Rinalda Prawikasena; Aning Sofyan (UNISBA Press, 2022)
Abstract. Film is one of the means of entertainment in which there is a story or event from a true or fictional story. Film is also a means of education, information as well as distribution of works of art. Along with the development of the times, many films were produced with horrific themes such as violence, death and other terrible things. Therefore, the researcher chose the film